Effect of volleyball modification on Insuline-Like Growth Factor -1 in prepubertal children - Endah Krisnawati; Shoffurijal Agyanur (Universitas Sriwijaya, 2023)
This study aims to determine the effect of volleyball game modification on insuline-like growth factor-1 hormone levels in prepubertal children. The method used The Randomized Pretest-Posttest Group Design using formula techniques by Higgins and Kleinbaum, with the results of 20 subjects. And divided into 2 groups based on inclusion and exclusion criteria. The experimental group was given the invention of the modification of the volleyball game and the control group without treatment. Blood is taken 24 hours before the exercise intervention and 24 hours after the intervention. Modification of the volleyball game was carried out for 6 weeks with 3x interventions in 1 week. Serum data results analyzed with SPSS 25. The results of the One-Way Anova test of the modification group with the control group showed a p value of 0.000 (P<0,05). meanwhile, in the Paired Sample T-Test test for the initial test and the final test in the volleyball game modification group, the p value is 0.000 (P<0,05). This study can be concluded that there was a significant influence of volleyball game modification on the increase in IGF-1 levels in prepubertal children with a value of P = 0.000 (P < 0.05).